A feasibility study of an educational program on obstetric danger signs among pregnant adolescents in Tanzania: A mixed-methods study. (2018) - Mwilike, Beatrice; Shimoda, Kana; Oka, Miyuki; Leshabari, Sebalda; Shimpuku, Yoko; Horiuchi, Shigeko
Abstract: Background: In Tanzania, adolescents have a high lifetime risk of dying from pregnancy and childbirth complications. Objective: To determine the feasibility of an education program in improving knowledge of obstetric danger signs and promoting appropriate healthcare-seeking behavior, as well as encouraging the development of a peer network support group. Methods: An embedded mixed-methods design was used. This research was a pilot study conducted in a health facility in rural Tanzania. Quantitative data was collected before and after the education program using questionnaires. Focus group discussion was used to collect qualitative data. Results: 15 pregnant adolescents between 15 and 19 years of age participated. Their median age was 18.0 years (SD ± 1.19), and 66.7% were ≤18 years. There was a significant increase in the scores of knowledge of danger signs during pregnancy between the pre-test (M = 7.20, SD = 2.83) and the post-test (M = 9.07, SD = 1.67); t = 2.168, p = 0.048. There was a significant strong positive correlation between the healthcare-seeking behavior score and social support score variables [r = 0.654, p = 0.008]. The education program was feasible in terms of implementation, acceptability, and demand as indicated by its >84% score. Four categories were identified from the qualitative data: "supportive family", "rejection and abortion", "support from peers", and "potential barriers to seek care". Conclusion: The development of an education program particularly on obstetric danger signs was feasible and helpful for pregnant adolescents in Tanzania.